Asynchronous online lecture may not be an effective method in teaching cardiovascular physiology during the COVID-19 pandemic - Kositanurit, Weerapat; Vivatvakin, Sarocha; Kaikaew, Kasiphak; Varachotisate, Pachara; Burana, Chuti; Chayanupatkul, Maneerat; Thanprasertsuk, Sekh; Wangsaturaka, Danai; Kulaputana, Onanong (BMC medical education, 2022)
Background Asynchronous online lecture has become a common teaching method in medical education, especially during the COVID-19 pandemic. However, the effectiveness and students’ attitudes towards this method under this special circumstance have not been exclusively studied. Hence, we aimed to evaluate these aspects of cardiovascular physiology teaching in an undergraduate medical curriculum. Methods We analysed and compared the academic achievement and attitudes of 613 medical students on cardiovascular physiology between pre-COVID-19 and COVID-19 years in which different teaching methods were implemented. In addition, we also explored the importance of teaching methods and teachers by subgroup analysis to evaluate whether they influenced the academic achievement and attitudes of students. Results Overall students’ academic achievement was significantly higher when lectures were taught by the traditional method than by the asynchronous online method. Moreover, subgroup analysis revealed that teachers were also a factor influencing students’ academic achievement. Although most students had positive attitudes towards asynchronous online lectures, overall satisfaction was slightly higher when all lectures were taught by the traditional method than by the asynchronous online method. Conclusions Asynchronous online lectures might not be an effective teaching method especially during the abrupt change in education. Under the ‘new normal’ medical education, not only teaching methods but also teachers are the essential keys to the success in academic achievement and attitudes of undergraduate medical students.